2020
DOI: 10.3390/antiox9090790
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory, Antioxidant, and Antifibrotic Effects of Kefir Peptides on Salt-Induced Renal Vascular Damage and Dysfunction in Aged Stroke-Prone Spontaneously Hypertensive Rats

Abstract: The increased prevalence of renal dysfunction and chronic kidney disease (CKD) and the high costs and poor outcomes of treatment are a significant health issue. The consequence of chronic high blood pressure is the increased prevalence of target organ end-stage renal disease, which has been proven to be a strong independent risk factor for adverse cardiovascular disease. A previous study showed that kefir products have anti-inflammatory and anti-hypertensive activities and immunological modulation functions. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The study showed that the kefir peptides administration at both doses (150 mg/kg and 500 mg/kg) reduced PM4.0-induced inflammatory cell infiltration and inflammatory mediators' expression such as TNF-α, IL-lβ, and IL-4 in lung tissue by inactivating NF-κB signaling. Following the current finding in 2020, Chen et al [122] further studied the effects of the kefir peptides against oxidative stress and inflammation and their protective ability against renal dysfunction on aged salt-induced stroke-prone spontaneously hypertensive (SHRSP) rats. The study revealed a decrease in renal infiltration of inflammatory cells; reactive oxygen species (ROS) levels; histopathological lesions; and the release of vascular cell adhesion molecule-1 (VCAM-1), monocyte chemoattractant protein-1 (MCP-1), endothelin-1 (ET-1), and the cytokine nucleotide-binding oligomerization domain (NOD)like receptor family pyrin domain containing 3 (NLRP3) and transforming growth factor-β (TGF-β) in salt-induced SHRSP rats.…”
Section: Anti-inflammationmentioning
confidence: 94%
“…The study showed that the kefir peptides administration at both doses (150 mg/kg and 500 mg/kg) reduced PM4.0-induced inflammatory cell infiltration and inflammatory mediators' expression such as TNF-α, IL-lβ, and IL-4 in lung tissue by inactivating NF-κB signaling. Following the current finding in 2020, Chen et al [122] further studied the effects of the kefir peptides against oxidative stress and inflammation and their protective ability against renal dysfunction on aged salt-induced stroke-prone spontaneously hypertensive (SHRSP) rats. The study revealed a decrease in renal infiltration of inflammatory cells; reactive oxygen species (ROS) levels; histopathological lesions; and the release of vascular cell adhesion molecule-1 (VCAM-1), monocyte chemoattractant protein-1 (MCP-1), endothelin-1 (ET-1), and the cytokine nucleotide-binding oligomerization domain (NOD)like receptor family pyrin domain containing 3 (NLRP3) and transforming growth factor-β (TGF-β) in salt-induced SHRSP rats.…”
Section: Anti-inflammationmentioning
confidence: 94%
“…In this study, we found that the levels of Ednra were significantly increased in the myocardial tissue of MCMV-infected mice, but significantly decreased with miR-1929-3p overexpression, suggesting that miR-1929-3p may influence remodeling of the hypertensive myocardium induced by MCMV infection through its target gene Ednra. Chen et al demonstrated that kefir peptides can exert anti-inflammatory and antifibrotic effects on target organs of spontaneous hypertension by simultaneously reducing the expression of ET-1 and NLRP3 [ 37 ]. Bao et al found that Coxsackie virus B3 can activate inflammatory bodies and induce viral myocarditis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the recent COVID-19 viral outbreak calls for non-conventional antiviral agents aiming to reduce the risk of infections and promote patient recovery [64]. Scientific research data support the claim that the regular consumption of kefir can be associated with a wide range of health-promoting affects (Figure 3), including anti-carcinogenic [87], anti-oxidant [89], anti-inflammatory [90], antifibrotic [91], anti-microbial [92], and anti-diabetic [93] effects, as well as improved digestion [94] and lactose tolerance [95], and more recent findings support the link between kefir's probiotic strains and bio-functional metabolites and an enhanced immune system and antiviral activities [65,96]. es 2021, 7, x FOR PEER REVIEW 11 of 15 Boosting and stimulating the immune system is one of the most effective strategies to prevent infections caused by many different pathogens, including viruses [1,12].…”
Section: Future Prospects Towards Health-promoting Effectsmentioning
confidence: 92%